Fixing de Morgan’s Laws in Counterfactuals - Romoli, Jacopo; Santorio, Paolo; Wittenberg, Eva (Proceedings of the Amsterdam Colloquium, 2019)
Classical semantics for counterfactuals are based on a notion of comparative similarity. These semantics are intensional, hence they predict that logically equivalent clauses can be substituted in counterfactuals salva veritate. A recent truth-value judgment study by Ciardelli, Zhang, and Champollion ([6]; CZC) appears to challenge both the idea that com parative similarity plays a role in counterfactual semantics and the prediction that logical equivalents are substitutable. CZC account for their data via an inquisitive semantics for disjunction and a semantics for counterfactuals that does not exploit the standard similar ity algorithm. We report on a study consisting of two experiments that start from CZC’s general idea, but use a simpler scenario, manipulate negation more systematically, and add an extra task based on the selection of pictures. Our results replicate the differences found by CZC, but they also suggest that the effect is linked to the presence of overt negation rather than disjunction. We conclude that (i) inquisitive disjunction is neither necessary nor sufficient to account for the problem in full generality, and (ii) the evidence does not encourage rejecting a similarity semantics.